Bring Back Our Girls, social mobilization: implications for cross-cultural research - Olutokunbo, Adekalu Samuel; Suandi, Turiman; Cephas, Oluwasetitan Rotimi; Abu Samah, Irza Hanie (International Institute for Science, Technology & Education, 2015)
Social mobilization is a proactive measure for community development that salvages the society from destruction and disaster. From sociological perspective, this paper discusses the concept of social mobilization and its implications for cross-cultural research. To do this, the study uses the “Bring Back Our Girls” Global Campaign, as the focal point of discussion, which has currently become a global phenomenon, in Africa, Asia, Australia, Europe, North America, and South America. To achieve the primary objective, this study adopted the method of content analysis of relevant existing literature; materials, pictures, as well as news reports to draw up conclusion based on the subject matter. The study revealed the importance of unity among nations, in the campaign for “Bring Back Our Girls”, in the midst of religious turmoil, different cultures, gender inequalities, and ethnic diversities. However, while waiting for the return of more than 200 girls abducted from their dormitories at the Government Girls’ Secondary Schools, Chibok, Borno State, North-East Nigeria, by the out-of-control members of the Boko Haram sect, it is needful that, nations keep recognizing the vital roles of social mobilization in bringing positive changes to the society. By implication, the study recognizes the importance of, and a clarion call for further cross-cultural research which goes beyond geographical, religious, political, and cultural jurisdictions. Recommendations on utilizing the knowledge of social mobilization movement campaign for the advancement of society were made.